Metacognitive Awareness Strategies For Listening Comprehension - -Chin, Ch’ng Looi; Unin, Norseha; Johari, Aiza (AJELP: Asian Journal of English Language and Pedagogy, 2017)
Language educators tend to focus extensively on reading and writing skills. Listening activities are often carried out only to test the students’ abilities which may lead to their anxiety and apprehension (Vandergrift, 1999). Generally, many students face difficulty in their listening assessments. Students need to apply certain mental steps or operations in listening to encounter their listening problems. These mental steps are referred to as strategies to assist the learners to achieve a reasonable listening comprehension (Goh, 2002).This study is designed to identify the students’ levels of Metacognitive Awareness Strategies in performing their listening tasks and to examine the influence of the strategies on their test scores. The study was conducted in two stages of Pre-test and Post-test, where 100 participants were selected based on a convenience sampling. After submitting their Pre and Post-tests, they were required to complete a Metacognitive Awareness Listening Questionnaire (MALQ), developed by Vandergrift et al. (2006). Overall, the findings show an increase in the percentage of correct answers for the listening comprehension task, based on the MCQ given. The findings reveal that metacognitive strategy awareness has a positive effect on students’ test scores. ESL teachers can enhance the use of MALQ strategies for listening comprehension. Further research is necessary to study how metacognitive strategies affect the students’ listening performance, as well as, to conduct interventions that will encourage metacognitive awareness.